Synthesis, Characterisation and Antiproliferative Studies of Allyl(dicarbonyl)(cyclopentadienyl)molybdenum Complexes and Cyclodextrin Inclusion Compounds. Issue 29 (19th August 2014) - Braga, Susana S.; Mokal, Vijaya; Paz, Filipe A. Almeida; Pillinger, Martyn; Branco, Ana F.; Sardão, Vilma A.; Diogo, Cátia V.; Oliveira, Paulo J.; Marques, Maria P. M.; Romão, Carlos C.; Gonçalves, Isabel S.
Abstract: The complexes [(η 5 ‐C5 H4 –CO–R)Mo(CO)2 (η 3 ‐C3 H5 )] [R = OH (1 ), Phe–OMe (2 )] have been examined as guests for the cyclodextrin (CD) hosts β‐CD and heptakis(2, 3, 6‐tri‐ O ‐methyl)‐β‐CD (TRIMEB), and the resultant inclusion compounds have been characterised in the solid state by elemental and thermogravimetric analyses, powder X‐ray diffraction, 13 C{ 1 H} cross‐polarisation (CP) magic angle spinning (MAS) NMR spectroscopy and FTIR spectroscopy. Single‐crystal X‐ray analysis of1 shows that the unit cell contains centrosymmetric supramolecular dimers comprising two dicarbonyl complexes linked through hydrogen‐bonding interactions involving the carboxylic acid groups. In screening tests for antiproliferative effects, the CD adducts containing1 displayed enhanced antitumour activity against mouse melanoma (when compared with nonincluded1 ), while showing minimal activity towards human adenocarcinoma and nontumour rat myoblast cell lines. TRIMEB encapsulation resulted in a predominant toxic effect on tumour cells versus the non‐neoplastic myoblast cells. Abstract : The crystal structure of [(η 5 ‐C5 H4 –COOH)Mo(CO)2 (η 3 ‐C3 H5 )] (1 ) is presented. Both1 and its phenylalanine derivative were included into β‐cyclodextrin (CD) and per‐ O ‐methylated β‐CD (TRIMEB). Overall, the inclusion contributed to a higher and more specific action on tumour cells, thereby lowering deleterious effects on a healthy myoblast line.